2020
DOI: 10.5937/jomb0-27554
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein as an early predictor of COVID-19 severity

Abstract: Background: Data for predicting severity of patients with COVID-19 infection are sparse and still under investigation. We retrospectively studied whether the admission serum C-reactive protein level (CRP) can serve as nearly predictor of disease severity during COVID-19 infection in comparison with other hematologic and inflammatory markers. Methods: We included all consecutive patients who were admitted in Cheikh Khalifa International University Hospital, Casablanca, Morocco, between February to April 2020, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
78
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 27 publications
(26 reference statements)
13
78
2
5
Order By: Relevance
“…According to the published data [ 4 , 5 , 23 , 26 ], comorbidities, such as hypertension, diabetes mellitus, and obesity, are risk factors for a severe course of COVID-19. We investigated the effect of these comorbidities on the length of hospital stay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the published data [ 4 , 5 , 23 , 26 ], comorbidities, such as hypertension, diabetes mellitus, and obesity, are risk factors for a severe course of COVID-19. We investigated the effect of these comorbidities on the length of hospital stay.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite numerous studies indicating a close relationship between lymphopenia and disease severity, we did not find significant differences in the lymphocyte count in groups of patients with differing severity of COVID-19 in our cohort. Many researchers have suggested considering the C-reactive protein (CRP) as a prognostic factor [ 3 , 36 ], a high level of which is associated with a worsening of the disease. A number of studies [ 3 , 5 , 37 ] have reliably demonstrated a significant increase in the blood CRP level in criticalcondition patients.…”
Section: Resultsmentioning
confidence: 99%
“…16 Study from Chen et al, 2020 shown the level of plasma CRP was positively correlated to the severity of COVID-19 and study from Ahnac et al found that the CRP level at administration represent a simple and independent factor that ca be useful for early detection of severity COVID-19. 17,18…”
Section: Discussionmentioning
confidence: 99%
“…C-reactive protein, an acute-phase inflammatory protein, reported to be used as a predictor of severity of COVID-19 infection [ 28 ]. Another striking observation in our study is that the diabetic subset had higher admission CRP levels than the total cohort (74.7 mg/L vs 50.65mg/L).…”
Section: Discussionmentioning
confidence: 99%